"Let Me Show You How Nice I Am": Impression Management as Bias in Empathic Responses. Issue 6 (August 2020) - Sassenrath, Claudia
Past research showed that empathic responses are confounded with social desirability. The present research aims at illuminating this confound. In a first step, it is examined how a measure typically implemented to screen, for response, biases based on social desirability (i.e., the Balanced Inventory of Desirable Responding) relate to classical measures of interindividual differences in empathic responses (i.e., the Interpersonal Reactivity Index). Moreover, it is investigated what happens to empathic responses under conditions of reduced opportunity to behave socially desirable. Results of two correlational studies indicate that impression management (IM) as well as self-deceptive enhancement as facets of a socially desirable response bias is related to self-reported empathic responses. Results of an additional experiment show that introducing conditions reducing opportunity for IM lowers empathic responses toward a person in need. Implications for research on self-reported empathy and empathy-induced prosocial behavior are discussed.